(untitled) (The Research of Medical Science Review, 2025)
Introduction Severe Acute Malnutrition (SAM) and Protein Energy malnutrition (PEM) in under- five children are a serious concerns accounting for a huge number of child mortality and disease burden each year. Despite great efforts Pakistan still face a chronic and severe under- five malnutrition that need to addressed through sustainable solutions. Objectives: The current Randomized control Trial was based on the following objectives. 1.To determine the efficacy of dietary enrichment of zinc in the RUTF among children with PCM. 2.To investigate the effects of dietary zinc source supplementation on the weight gain, states of dermatitis and oedema among children with SAM during the recovery. Methodology: This study was conducted at the stabilization Units of Khyber Teaching Hospital, Peshawar. Based on written and informed consent a sample of 100 SAM children were divided equally into a control group where they receive the standard protocols and an experimental group which receive the standard protocol along a RUTF khtichri with the value addition of sunflower and pumpkin seed flours (being prepared under standard laboratory procedures). The effects were observed on the weight gain, oedema, and dermatitis. Results: Results of the current indicated that 96% of the children belonged to rural background with both parents largely being illiterate, living in an extended family system (68%) and a larger family sizes. The household conditions exhibited a number of probable factors leading to unhygienic environments. The feeding profiles of the children showed that 22% were exclusively breast fed while 68% received a diluted formula or cow’s milk with added sugars. About 40% children were partially vaccinated and 96% children were not given timely complementary feedings. Overall, 76% children were born with normal weight but suffered severe concurrent diarrhea. The anthropometric data indicated severe acute malnutrition with mean Z Score of 4.28± 4.09 which declined to 2.6 ± 2.63 in the control and 1.91 ± 2.11 in the experimental group which was significantly different from both pre-test and post-test of the control group. The dermatitis in both the groups improved but the results were more promising for the experimental group (64% no dermatitis) at discharge. The similar trend was also observed in the oedema where 78% severe generalized edematous children improved but in a more promising manner in the experimental group. Conclusion: the study concludes that the safe addition of value addition of the local, nutrient rich food source to the complementary feeds of the SAM and PCM children help overcome child malnutrition in a more sustainable manner.